Together we deliver 50 stories of ADB partnerships in Asia and the Pacific. (Development effectiveness review., 2017)
This special edition of Together We Deliver tells 50 stories that highlight the importance of good partnerships in Asia and the Pacific in meeting the complex development challenges of our dynamic region